Makna Hubungan Beda Agama Dalam Perspektif Islam Pada Film Akhirat A Love Story Karya Jason Iskandar - Assidiqi, Dikri; Masruroh, Sayidah Afyatul (Menara Tebuireng, 2023)
Film is an effective medium for conveying a message. But not every message can be conveyed properly; therefore, it is necessary to formulate the research problem: (1) What is the meaning of the sign of the relationship between different religions from an Islamic perspective in the film Akhirat: A Love Story? This study uses a qualitative approach, with the method used being Roland Barthes' semiotic analysis of "the meaning of the relationship between different religions from an Islamic perspective in the film Akhirat: A Love Story by Jason Iskandar". In this study, Roland Barthes' theory is very relevant for interpreting the sign structure in the film Akhirat: A Love Story. Roland Barthes classifies significance in two stages, namely denotative meaning and connotative meaning. Roland Barthes also adds myth, which is the signifier and has the deepest meaning. Then the analysis in this film is focused on the relationship between different religions, which is the formulation of the problem in this study. From the results of the meaning of the sign structure contained in the film Akhirat: A Love Story, there are several scenes about the relationship between different religions. Then these aspects are analyzed from the perspective of the Islamic religion, with the aim that this research can provide knowledge about interfaith relations. Islam prohibits anyone who does this, which is supported by several arguments in the Qur'an and hadith. Keyword: Film, Interfaith Relations, Islamic Perspective